Cyanobacteria in Biological Soil Crust of Chadormalu Area, Bafq Region in Central Iran - Moghtaderi, A.; Taghavi, M.; Rezaei, R. (Pakistan Journal of Nutrition, 2009)
Arid and semi-arid regions are characterized by sparse vegetation or absence of vegetation cover. The absence of a dense distribution of macrophytes (higher plants), much of arid and semi-arid surfaces are covered by microphytic communities of small non-vascular plants. An important group of organisms comprising soil crusts in such habitats are cyanobacteria. In this research the genus and species of cyanobacteria were detected at the Chadormalu desert, Yazd Province of Iran. The study showed that cyanobacteria (Microcoleous vaginatus, Nostoc.sp, Microcystis.sp, Ocillatoria.sp, Chroococcuss.sp, Chroococcidiopsis, Ocillatoria.sp, Chroococcuss.sp, Microcystis.sp) at Chadormalu Desert are comparable with other Deserts in cold and warm dry conditions.